RÉPTEIS DO REFÚGIO DE VIDA SILVESTRE MATAS DO SISTEMA GURJAÚ, PERNAMBUCO – BRASIL - Silva, Tulíbia Laurindo; Barbosa, Gessica Gomes; Oliveira, Camila Nascimento de; Rodrigues, Gilberto Gonçalves (Revista Nordestina de Zoologia, 2017)
The Atlantic Forest is characterized by being one of the world's hotspots. Regarding the studies directed to reptiles in the Atlantic Forest biome, there is a need to create lists of species, ecological studies and about conservation status. The objective of this work was to inventory the species of reptiles of the Matas Wildlife Refuge of the Gurjaú System (RVS Gurjaú) located between the municipalities of Moreno, Jaboatão dos Guararapes and Cabo de Santo Agostinho. The study was conducted between March 2015 and April 2016 , durante 12 months. Two capture methods were used: active search limited by time and passive search. Twenty-one species, 20 genera and 15 reptile families were recorded. Between the species an exotic species was recorded the Hemidactylus mabouia lizard and an endemic species of the Atlantic Forest, Gymnodactylus darwinii. Regarding the dry / rainy period, most species were found in the rainy season, with only five species recorded during the dry period. The registered species, none are threatened or vulnerable. This study highlights the importance of the conservation of forest remnants filling the gaps on the knowledge of reptiles in the State of Pernambuco.